HEALTH PROMOTION IN EFFORTS TO INCREASE MEDICATION COMPLIANCE IN HYPETENSIVE PATIENTE: A LITERATURE REVIEW - NONE, FRANSISCA LISA; Musharyanti, Lisa (Universitas Respati Yogyakarta, 2021)
Compliance to taking medication is one of the problems in disease control efforts, especially non-communicable diseases such as hypertension. Taking medication regularly is one of the keys to control hypertension. One of the efforts to improve medication adherence is health promotion. The purpose of this study is to determine the methods used in health promotion to increase medication adherence in hypertensive patients. This research is a literature review. Sources of research articles were taken from the PubMed, Science Direct, and the Cochrane Library database, with the keywords